Intestinal Perforation with Ingestion of Blunt Foreign Bodies: A Case Report - Lok Bahadur Kathayat; Anup Chalise; Jemesh Singh Maharjan; Jasmine Bajracharya; Ritesh Shrestha (Journal of Nepal Medical Association, 2022)
Foreign body ingestions are fairly common and present with obvious symptoms. Certain foreign bodies, like button batteries and magnets, are rarely ingested, but carry with them the extremely dangerous risk of bowel wall necrosis, intestinal perforation and fistula formation. Suspected cases of such ingestions require a high index of suspicion and any delay should be avoided once a diagnosis is made. Herein, we report a case of a 7-year-male patient who presented with abdominal pain and vomiting following similar foreign body ingestion, which resulted in multiple small bowel perforations. The foreign body was removed by a laparotomy, and the affected bowel segments were resected and anastomosed. The patient made an uneventful recovery and was discharged after 5 days.